Pengaruh Diversifikasi Industri Terhadap Manajemen Laba Dengan Komisaris Independen Sebagai Variabel Moderasi - Mutmainah, Siti; Aprilia, Zulfa (Jurnal Akuntansi dan Governance Andalas, 2021)
The purpose of this study is to examine the effect of industrial diversification on earnings management with independent commissioner as a moderating variable. The independent variable used in this study is industrial diversification measured using 1-Herfindahl Hirschman Index (1-HHI). The dependent variable in this study is earnings management which is measured using absolute discretionary accruals from the modified Jones model. Later, the moderating variable of independent commissioner is measured using three proxies that is the proportion of independent commissioners, the average level of attendance of meetings, and educational background. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. This study used purposive sampling method to collect the data and obtain a total of 108 research samples consisting of 27 companies for 4 years. The test analysis used multiple linear regression analysis models and moderated regression analysis (MRA). The result of this study indicates that industrial diversification has a significant positive effect on earnings management. Then, the proportion of independent commissioners and the average level of attendance of independent commissioners in meetings cannot weaken the relationship between industrial diversification and earnings management. Meanwhile, the educational background of independent commissioners can weaken the relationship between industrial diversification and earnings management.